Trade Facilitation Framework for E-commerce Platforms using Blockchain - Shaalan, Khaled (2019)
Electronic commerce (e-commerce) platforms have revolutionized the international trading business. E-commerce trading market is rapidly expanding over time. This expansion urges exploring the e-commerce trading process to support the continuous growth of this domain. An essential component of this process is how customs administrations manage the cross-border e-commerce trade. In this paper, a blockchain-based framework is proposed. The aim of this framework is to streamline the e-commerce trading process through the use of blockchain technology. This will ease and fulfil the customs administrations duties using advance electronic data that are made available by adopting the inherited features of the blockchain technology. This framework supports the expanding e-commerce market, governs how e-commerce stakeholders transact, and establishes a trust level among these stakeholders. The proposed framework has been evaluated using the System Usability Scale (SUS). The overall SUS results show that the system is highly acceptable by all users’ categories.